Some properties of connections on iterated tangent bundles - Kureš, M. (Archives of Mechanics, 1998)
Possibilities of a generalization of the original Grifone's approach to connections are studied. Seinisprays associated to connections and torsions on the iterated tangent bundle TTM are described.